2007
DOI: 10.1063/1.2736388
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a heat flux sensor using short pulse laser calibration

Abstract: A method to calibrate classical heat flux sensors is presented. The classical approach to measure the temperature inside a known material by using a thermocouple fails when the measurement time is very short. In this work the surface heat flux is determined by solving the inverse heat conduction problem using a noninteger identified system as a direct model for the estimation process. Using short pulse laser calibration measurements the crucial design aspects of the sensor that play a significant role when ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 1 publication
0
15
0
Order By: Relevance
“…Battaglia et al showed that this model holds for many analytically known problems and only recently, the NISI method has been applied to the classical problem of null-point calorimetry. [1][2][3] In this paper, an analysis of the characteristic feature of the identified system, the impulse response, is described. It is shown that the impulse response changes representatively when certain parameters of the system change and relations can be found, so that the impulse response can serve as a direct tool.…”
Section: Introductionmentioning
confidence: 99%
“…Battaglia et al showed that this model holds for many analytically known problems and only recently, the NISI method has been applied to the classical problem of null-point calorimetry. [1][2][3] In this paper, an analysis of the characteristic feature of the identified system, the impulse response, is described. It is shown that the impulse response changes representatively when certain parameters of the system change and relations can be found, so that the impulse response can serve as a direct tool.…”
Section: Introductionmentioning
confidence: 99%
“…In the following the calibration method for the FIPEX sensors is detailed. The PHLUX sensors were calibrated for the incident heat flux density using the NISI (non-integer system identification) method (Löhle et al, 2013(Löhle et al, , 2007. A microwave generator (2.45 GHz, Sairem, France) is used to produce a low-pressure oxygen plasma as a source of atomic oxygen, a technique widely employed in various technical and scientific applications and well studied in the literature (Lebedev, 2010).…”
Section: Calibrationmentioning
confidence: 99%
“…In order to apply this approach, the methodology consists first in identifying the thermal behavior of the sensor according to relation (2). This stage can be viewed as a calibration of the sensor.…”
Section: Theorymentioning
confidence: 99%
“…Transient heat flux measurements are widely used when time resolution is required or harsh environments do not allow steady-state sensor technique [1], [2]. The principle of the present sensor is to measure the temperature inside an appropriate material which is part of the heat flux sensor and to estimate the heat flux from inverse heat conduction calculation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation